Survival and revival of Catalan civil law. From the Nueva Planta Decree to the Civil Code of Catalonia - Albert Lamarca i Marquès (Catalan Historical Review, 2025)
This article outlines the evolution of Catalan law over the three centuries spanning from the Nueva Planta Decree (1716) to the approval of the last book of the Civil Code of Catalonia (2017). During this time, Catalan law survived despite the Spanish State’s various attempts to suppress it and to legally assimilate Catalonia into the law of Castile. The tenacity and perseverance of both Catalan jurists and Catalan society as a whole made it possible to conserve and revive this law, which is one of the features shaping Catalan identity.